1979
DOI: 10.1080/01638537909544465
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of lookbacks during studying∗

Abstract: Looking back at relevant sections of previously read text is proposed as a useful fixup strategy when comprehension fails while studying a text.Subjects read 24 pages of text and answered inserted questions which assessed their comprehension of the text. About half of the subjects were branched back to reread prerequisite information when it was later needed but had not been fully understood by those subjects. Subjects receiving lookbacks showed better comprehension of later information dependent upon the prer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…Nevertheless, inducing readers to use a lookback strategy apparently has beneficial effects. Alessi et al (1979) reported improved test performance among students who were induced to reread sections of text containing information about which they had answered questions incorrectly.…”
Section: Regulation Of Comprehensionmentioning
confidence: 95%
“…Nevertheless, inducing readers to use a lookback strategy apparently has beneficial effects. Alessi et al (1979) reported improved test performance among students who were induced to reread sections of text containing information about which they had answered questions incorrectly.…”
Section: Regulation Of Comprehensionmentioning
confidence: 95%
“…Although rereading has been shown to increase comprehension of text information (Alessi, Anderson, & Goetz, 1979;Bernhardt, 1983;Flood, 1986) and may be necessary for developing well-integrated memory representations in naturally occurring texts, which are often inconsiderate (Armbruster, 1984), it is only one of several strategies that students may employ to comprehend texts. In future studies, students' use of other strategies important for sentence integration such as inferencing and reinstatement of previously presented information into working memory should be explored.…”
Section: Limitations Of the Present Study And Suggestions For Future mentioning
confidence: 99%
“…Research that has examined one process or the other has often failed to distinguish between the two. (Alessi, Anderson, & Goetz, 1979;Baker & Anderson, 1982).…”
Section: Cecil Smith Northern Illinois Universitymentioning
confidence: 97%